Vaccination in India: An Insight - Avishek Das; Tapas Kumar Chaudhuri (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
This review has documented the vaccination in India and the history of it with a view to know the directions of developing indigenous vaccines for expanding  the benefit  to the grass root level in this highly populated country. Expansion of smallpox vaccination, typhoid vaccine trial and setting up of vaccine institutes were witnessed in the early twentieth century in almost each state in India. A number of private vaccine manufacturers came up in the post independence period in India besides the establishment of BCG vaccine in National Institutes. Smallpox vaccination was continued till it was eradicated and the country became smallpox free in 1977. Universal Immunization Programme was launched in 1985 as a part of the expanded programme of immunization which was established in 1978.India has declared as the country of non-endemic for poliomyelitis in 2012. Therefore, the immunization efforts are guided by the experience of the past events for analyzing and developing vaccines in the present time.